Identifikasi Jenis, Makna, dan Fungsi Paribasa Bali dalam Cerpen 'Begal' Karya I D. K. Raka Kusuma serta Relevansinya dengan Pembelajaran Bahasa Bali di SMA - Ni Luh Novi Panca Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
Balinese paribasa is used to beautify and sweeten various Balinese discourses including Balinese short stories. In addition, Balinese paribasa is also used to reveal the values of education, morals, and social criticism in Balinese short stories that can be used as a guideline in life. Therefore, the researcher is interested in researching Balinese paribasa in the short story Begal by I D. K. Raka Kusuma. The theoretical foundations used in this study are Balinese paribasa theory, Balinese short stories, meaning theory and function theory. This research is a qualitative research, using library study and interview methods, supported by the technique of reading, recording, and listening. The data analysis of this study uses the descriptive method of analysis. The presentation of the data uses an informal method, namely presentation with words and sentences The results of this research show: (1) there are seven types of Balinese paribasa in the short story Begal by I D. K. Raka Kusuma, (2) there are four meanings and four functions of Balinese paribasa in the short story Begal by I D. K. Raka Kusuma, (3) there is a relevance of the short story Begal by I D. K. Raka Kusuma with the teaching of the Balinese language, especially Balinese paribasa in class X and class XI at the high school education level. Based on this conclusion, it is suggested that connoisseurs of Balinese short story literature can understand more deeply the action only to the type, meaning, and function but can be applied in daily life